Tea (Camellia sinensis) processing residues: Thermochemical characterization of stalks and off-grade leaves for renewable energy - Sergio Muñoz-Salazar; Valentina Cruz-Ospina; Eduardo Duque-Dussan (Center of Biomass & Renewable Energy (CBIORE), 2026)
Tea (Camellia sinensis) processing generates significant quantities of solid residues, particularly stalks and off-grade leaves, which remain underutilized despite their potential as renewable energy resources. Valorization of these residues as solid biofuels could support waste reduction, local energy supply, and circular economy strategies in tea-producing regions. This study presents a thermochemical characterization of tea processing residues with emphasis on stalks and off-grade leaves. Representative samples were collected from a commercial tea processing facility in Bandung, Indonesia, and analyzed through proximate analysis to determine moisture, volatile matter, ash, and fixed carbon, and ultimate analysis to quantify carbon, hydrogen, nitrogen, sulfur, and oxygen. Higher heating value was determined by bomb calorimetry, and net calorific value was calculated to assess practical energy availability under combustion conditions. Thermal behavior was evaluated using thermogravimetric analysis and differential scanning calorimetry to characterize degradation stages and combustion stability. Results showed volatile matter contents above 70%, carbon contents between 45% and 50%, and higher heating values ranging from 16 to 19 MJ·kg⁻¹. Corresponding net calorific values ranged from 15 to 18 MJ·kg⁻¹, comparable to widely used lignocellulosic biomasses such as coffee husk and sugarcane bagasse. Thermogravimetric profiles revealed distinct devolatilization and char oxidation stages. Differences between stalks and off-grade leaves confirmed the relevance of fraction-specific evaluation. These findings demonstrate that tea processing residues represent a viable solid biofuel resource for renewable energy applications in tea-producing regions.